Preferences for written corrective feedback among field-dependent and field-independent EFL Learners: A mixed-methods investigation - Mohamad Reza Farangi; Naser Rashidi; Mohamad Jokar (Social Sciences and Humanities Open, 2025)
Cognitive styles play a pivotal role in language acquisition, influencing learners' preferences for various learning strategies and techniques. This study examined the preferences of Field-Dependent (FD) and Field-Independent (FI) English as a Foreign Language (EFL) learners regarding the amount and types of Written Corrective Feedback (WCF). Using a mixed-methods design, data were collected from 135 Iranian EFL students recruited through stratified sampling based on academic level (undergraduate and graduate) at two universities. Participants completed the Group Embedded Figures Test (GEFT) to determine their cognitive styles and a validated WCF questionnaire to capture their feedback preferences. Quantitative data were analyzed using statistical techniques, including chi-square tests, independent-sample t-tests, and Pearson correlations, with effect sizes reported to ensure robust interpretations. Qualitative data from open-ended responses were analyzed thematically to uncover the underlying rationales for learners' preferences, ensuring a comprehensive understanding of the findings. Results indicated no significant correlation between cognitive styles and preferences for specific feedback amounts but revealed notable differences in preferences for certain types of WCF. Both FI and FD learners preferred their errors to be corrected. FI learners favored indirect feedback promoting autonomy, while FD learners preferred explicit corrections emphasizing teacher responsibility. Effectiveness of WFC was also a major recurring theme. These findings suggest that tailoring WCF to learners’ cognitive styles can enhance the effectiveness of feedback strategies. By addressing a critical gap in the literature, this study provides valuable insights for educators and curriculum designers, highlighting the importance of personalized approaches to feedback in EFL contexts.